Pengenalan Aksara Kaganga Lampung dengan Menggunakan Metode K-Nearest Neighbour (K-NN) - istiqphara, swadexi; Faida, Afida Nur; Darajat, Anisa Ulya (ELECTRON Jurnal Ilmiah Teknik Elektro, 2023)
Character recognition technology has been carried out using various artificial intelligence methods. In this paper, one of the artificial intelligence methods, namely K-nearest Neighbor (K-NN), will be proposed to recognize the kaganga script, which is the Lampung province script. The Lampung kaganga script is one of the Indonesian cultural assets from the native Lampung tribe. Currently, only a few people understand this Lampung kaganga script. Therefore, an effort is needed to preserve this character, one of which is through this research so that a computer application can be produced that helps in learning the Lampung kaganga script. In this paper, the recognition of the Kaganga Lampung script using the K-Nearest Neighbor (K-NN) will measure performance in terms of the recognition processing time and the recognition accuracy of this Lampung kaganga script. From the tests that have been carried out, the results obtained by using the K-NN method are able to recognize the kaganga Lampung character with an accuracy of 70% and the average time of the character recognition process is 1.1412 seconds.